Recent development of international water law: The Silala case - de Cossío Klüver, Manuel Augusto (2023)
In this text it is explored the broad and novel topic of the law applicable to international watercourses, also known as International Water Law. Reflecting on the conclusions of the United Nations Water Conference of 2023, as well as the documentation of the United Nations agencies related to water, we will analyze the development that the recent Judgment of the International Court of Justice of The Hague in the case Chile v. Bolivia on the status and use of the waters of the Silala has had for this new field of law.